2016
DOI: 10.1002/cncr.30134
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and diagnostic accuracy of the Patient‐Reported Outcomes Measurement Information System (PROMIS) item banks for routine surveillance of sleep and fatigue problems in ambulatory cancer care

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version record. Please cite this article as doi:10.1002/cncr.30134.This article is protected by copyright. All rights reserved. Accepted Article2 of the study, ethics application, recruitment, data management), Dobriyal A (conceptualization of the study, recruitment), Malik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 72 publications
(115 reference statements)
4
27
0
Order By: Relevance
“…Higher scores on this scale indicate higher levels of sleep disturbance. A T‐score greater than 57 was considered to represent a “clinically meaningful” sleep disturbance, as suggested in previous studies 19 …”
Section: Methodsmentioning
confidence: 99%
“…Higher scores on this scale indicate higher levels of sleep disturbance. A T‐score greater than 57 was considered to represent a “clinically meaningful” sleep disturbance, as suggested in previous studies 19 …”
Section: Methodsmentioning
confidence: 99%
“…In this large sample of patients with CRC, a quarter of the sample likely experienced clinically meaningful sleep disturbance at an average of 10 months after CRC diagnosis . The Month 10 RMM analyses showed that there were no latent classes driving the relationship between sleep disturbance and other patient, disease, and treatment characteristics.…”
Section: Discussionmentioning
confidence: 89%
“…In this large sample of patients with CRC, a quarter of the sample likely experienced clinically meaningful sleep disturbance at an average of 10 months after CRC diagnosis. 35 The they suggest that some patients will improve more than others based on the quality of their sleep disturbance as they transition off treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians should be attentive to symptoms related to CRF since they tend to be ignored, poorly managed and seldom reported by patients, because they assume that these symptoms are normal and temporary reactions to cancer treatment. Additionally, to ensure a routine screening for these and other symptoms, computerized adaptive testing can be used [13]. To overcome subjective measures with self-reporting questionnaires the evaluation of CRF can also be supplemented by recognizing step count and sleep times with smart bracelets to predict physical fatigue [14].…”
Section: Fatiguementioning
confidence: 99%